Hemodynamic monitoring in cardiogenic shock. Issue 4 (August 2021) - VanDyck, Tyler J.; Pinsky, Michael R.
Abstract : Purpose of review: Cardiogenic shock remains a major cause of mortality today. With recent advancements in invasive mechanical support strategies, reperfusion practice, and a new classification scheme is proposed for cardiogenic shock, an updated review of the latest hemodynamic monitoring techniques is important. Recent findings: Multiple recent studies have emerged supporting the use of pulmonary artery catheters in the cardiogenic shock population. Data likewise continues to emerge on the use of echocardiography and biomarker measurement in the care of these patients. Summary: The integration of multiple forms of hemodynamic monitoring, spanning noninvasive and invasive modalities, is important in the diagnosis, staging, initial treatment, and subsequent management of the cardiogenic shock patient.